Role of HCV Core gene of genotype 1a and 3a and host gene Cox-2 in HCV-induced pathogenesis - Ahmad Waqar; Ijaz Bushra; Khaliq Saba; Jahan Shah; Hassan Sajida (Virology Journal, 2011)
Abstract Background Hepatitis C virus (HCV) Core protein is thought to trigger activation of multiple signaling pathways and play a significant role in the alteration of cellular gene expression responsible for HCV pathogenesis leading to hepatocellular carcinoma (HCC). However, the exact molecular mechanism of HCV genome specific pathogenesis remains unclear. We examined the in vitro effects of HCV Core protein of HCV genotype 3a and 1a on the cellular genes involved in oxidative stress and angiogenesis. We also studied the ability of HCV Core and Cox-2 siRNA either alone or in combination to inhibit viral replication and cell proliferation in HCV serum infected Huh-7 cells. Results Over expression of Core gene of HCV 3a genotype showed stronger effect in regulating RNA and protein levels of Cox-2, iNOS, VEGF, p-Akt as compared to HCV-1a Core in hepatocellular carcinoma cell line Huh-7 accompanied by enhanced PGE2 release and cell proliferation. We also observed higher expression levels of above genes in HCV 3a patient's blood and biopsy samples. Interestingly, the Core and Cox-2-specific siRNAs down regulated the Core 3a-enhanced expression of Cox-2, iNOS, VEGF, p-Akt. Furthermore, the combined siRNA treatment also showed a dramatic reduction in viral titer and expression of these genes in HCV serum-infected Huh-7 cells. Taken together, these results demonstrated a differential response by HCV 3a genotype in HCV-induced pathogenesis, which may be due to Core and host factor Cox-2 individually or in combination. Conclusions Collectively, these studies not only suggest a genotype-specific interaction between key players of HCV pathogenesis but also may represent combined viral and host gene silencing as a potential therapeutic strategy.